Improving Patient Compliance in Antidepressant Therapy through Counselling - A, Kumpakha; S, Bhattarai; S, Sharma; HC, Paudel (Indian Journal of Pharmacy Practice)
Lack of knowledge on antidepressant medication and negative attitude are barrier of compliance. This study was conducted with the aims to improve patient compliance in antidepressant therapy through counselling and to study patient attitude and belief toward depression and antidepressant using antidepressant compliance questionnaires. In this study 65 patients with moderate depression attending Psychiatry OPD at Kathmandu university teaching hospital were included. Participants were interviewed using antidepressant compliance questionnaires (ADCQ). Baseline scores on attitude and belief was obtained using ADCQ. Participants were counselled verbally with aid of leaflet. Improvement in compliance was accessed by follow up score after 2 weeks. Correlation coefficient between scores obtained using SPSS 19 at 0.05 level of significance. During the study period, 70.6% of participants were found to be complaint and took their medication as prescribed after 2 weeks of counselling. 66.7% of participants felt little informed about antidepressant and 58.8% were willing to continue antidepressant treatment. The correlation coefficient between category 1 of ADCQ and follow up score found to be r= 0.219; p=0.122(p>0.05). The correlation coefficient between category 3 and follow up score r=0.413; p=0.003 (p<0.01), r=0.315;p=0.024 (p<0.05) between category 4 and follow up score. Likewise correlation coefficient between total ADCQ scores and follow up after 2 weeks was found to be r=0.319; p=0.022 (p<0.05). It was concluded that the participants lack information about depression and antidepressants. Hence, they are suspicious about need of medication resulting in high dropout rate. Two weeks after counselling adherence was significantly improved.
Keywords: Antidepressants; Antidepressant compliance questionnaires; Counselling; Depression